3D extrusion free forming of geopolymer composites: Materials modification and processing optimization. (10th June 2020) - Sun, Chenchen; Xiang, Jichun; Xu, Mengxue; He, Yan; Tong, Zhangfa; Cui, Xuemin
Abstract: The key factors of 3D extrusion free forming of geopolymer composites were systematically investigated in this paper, which included the setting time, water retention capacity, rheological properties, mechanical performance and drying shrinkage. Geopolymer composites are not only suitable for extrusion but also retain their shapes after 3D printing. The different amount of sodium carboxymethyl starch (CMS) and 50% of calcium carbonate were respectively selected as modifying admixture and coarse aggregate, which effectively increased the water holding capacity and the setting time at room temperature of observably expanded fresh pastes. When the added amount of CMS was between 4% and 6%, the corresponding plastic viscosity was between 10.08 and 10.42 Pa s, the yield stress was between 32.53 and 66.71 Pa, and the plastic could avoid water-solid separation during extrusion through a nozzle and meet the requirements of extrusion and molding. Through the mechanical testing of hardened 3D printed materials, these composite materials exhibited compressive and flexural strength. Due to both their suitable workability and mechanical properties, these geopolymer composite materials can be used in 3D free forming for fabricating construction materials, molds, crafts or other products. Graphical abstract: Image 1